Flexible composite scintillators based on ZnWO₄ micro- and nanopowders - Tinkova, V.S.; Yakubovskaya, A.G.; Tupitsyna, I.A.; Abashin, S.L.; Abashin, S.L.; Tretyak, S.O. (Технология и конструирование в электронной аппаратуре, 2019)
Nano-sized and micro-sized ZnWO₄ powders were obtained by different methods: hydrothermal synthesis with microwave heating, molten salt method, solid-state synthesis and сrushing of bulk crystals. Their morphological features were studied using transmission electron microscope and scanning electron microscope. The obtained nano- and micro-sized powders were used as fillers for flexible composite scintillators. The silicon rubber was used as a binder. The luminescent characteristics and scintillation performance of composite scintillators were measured. The dependence of scintillation performance of flexible scintillators on the morphological features of ZnWO₄ nanocrystallites was demonstrated. The flexible composite scintillator based on zinc tungstate obtained by solid-state synthesis with lithium nitrate addition was obtained and investigated. Its scintillation performance was close to that of a ZnWO₄ single crystal.